Primary thoracic extraskeletal osteosarcoma: a case report and literature review - Qian, Jie; Zhang, Xue-Yan; Gu, Ping; Shao, Jin-Chen; Han, Bao-Hui; Wang, Hui-Min (Journal of Thoracic Disease; Vol 9, No 12 (December 29, 2017): Journal of Thoracic Disease, 2017)
Primary extraskeletal osteosarcoma (ESOS) presenting in thoracic locations is very rare and associated with a poor prognosis. The current study presents a case involving a large anterior mediastinal mass, which was histologically confirmed as a primary osteosarcoma. The literature concerning primary thoracic ESOS is reviewed. A total of 60 cases were identified. The median age was 60 years (range, 14–93 years) and males were more prevalent among the reported cases (65%). Survival analysis revealed that the overall 5-year survival was only 22.3%. The majority of cases of thoracic ESOS presented in the lung (n=24, 40%), with others presenting in the mediastinum, pleura, or chest wall. The benefit of surgery, chemotherapy and radiotherapy was confirmed by Cox regression survival analyses.